Clinical effectiveness of embrace wetbond and clinpro as pits and fissure sealants in young permanent molars : Randomized clinical trial - Noha Abdullah Agina; Mahmoud Hamdy Eid; RandaYoussef Abdalgawad (Cairo : Noha Abdullah Agina, 2018)
Dental caries is the most common chronic disease inchildhood. New methods of caries prevention have been focusingon occlusal pit and fissure caries, as this type of caries havealways been the earliest and most prevalent of all types. Differenttypes of fissure sealants have been investigated, and it is a clearfact that clinical retention of sealants was found to be the factor ofhighest impact on caries prevention. However, achieving a successful and durable bonding procedure involves many steps, istechnique sensitive, and time consuming.This study was planned to evaluate sealant retention anddevelopment of caries Embrace wetbond and Clinpro.Clinprowas used as a conventional BIS-GMA unfilled resin andEmbrace wetbond is one of relatively recent introduced sealant tested to be used in moisture conditions and has physicalproperties similar to other commonly used sealant.Subjects and methods: - The criteria used to determine sealant status was ModifiedSimonsen's criteria, 1991 for evaluation of sealant retention anddevelopment of caries, which are relatively simple to follow.Starting follow up immediately after insertion (baseline) and a follow up periods: 2 month, 4 months, .6 months and scores ranging from score 0 to score 4. - A total number of thirty eight patients were selected fromoutpatient clinic in Pediatric and Public Health Department,Faculty of Dentistry Cairo University. Their ages ranged from 6-9 years
Thesis (M.Sc.) - Cairo University - Faculty of Oral and Dental Medicine - Department of Pedodontics
Issued also as CD
Keywords: Dental caries; Embrace wetbond and clinpro; Fssure sealants